Powder, metal member, electrical contact, powder manufacturing method, and metal member manufacturing method
Through high-frequency induction heating and atomization technology, the problem of high chromium content and uneven quality in electrical contact materials is solved, and the uniformity and electrical characteristics of electrical contact materials with high chromium content are achieved, and the vacuum circuit breaker is improved. performance.
Patent Information
- Application Number
- CN202380041845.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-06-08
- Filing Date
- 2023-04-03
- Publication Date
- 2025-01-03
AI Technical Summary
It is difficult to produce electrical contact materials with high chromium content and excellent electrical characteristics in the prior art, and the powder quality is prone to deviations, resulting in poor uniformity and electrical characteristics of the electrical contact materials.
The high-frequency induction heating device is used to melt the raw material components, and the melting liquid is finely reduced into powder by atomization method to ensure uniform dispersion of copper and chromium, and control the particle size and composition standard errors of the powder to be within 1.2 to form a uniform matrix. and precipitate distribution.
It achieves excellent uniformity and electrical characteristics of electrical contact materials with high chromium content, and improves the performance of vacuum circuit breakers and the quality of electrical contacts.
Smart Images

Figure CN119255875A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to a powder, a metal component, an electric contact, a method for producing the powder, and a method for producing the metal component.
[0002] This application claims priority based on international application PCT / JP2022 / 023145 filed on June 8, 2022, and all the contents described in the above international application are cited herein. Background Art
[0003] Patent Document 1 discloses a method for manufacturing an electrical contact material for a vacuum circuit breaker or the like. The manufacturing method comprises: a step of obtaining a copper-chromium alloy powder in which chromium is dispersed in a copper matrix; and a step of sintering the copper-chromium alloy powder. The copper-chromium alloy powder is obtained by melting a mixture of copper and chromium and refining the molten liquid by an atomization method. The chromium content in the mixture is 5% by mass or more and 20% by mass or less.
[0004] The melting temperature of the mixture is the temperature at which the mixture becomes a liquid phase in the phase diagram of copper and chromium. By using an atomization method to refine the mixture in a liquid phase, particles with fine chromium precipitates dispersed in a copper matrix are obtained. The electrical contact material obtained by sintering such particles has uniform quality and excellent electrical properties.
[0005] Prior art literature
[0006] Patent Literature
[0007] Patent Document 1: Japanese Patent Application Laid-Open No. 4-95318 Summary of the invention
[0008] The powder disclosed herein is an aggregate of multiple particles containing a metal element, each of the multiple particles comprising a matrix and multiple precipitates dispersed in the matrix, the matrix comprising a first component, the multiple precipitates comprising a second component, the standard error of the content of the first component in the multiple particles being less than 1.2 based on mass, and the standard error of the content of the second component in the multiple particles being less than 1.2 based on mass. BRIEF DESCRIPTION OF THE DRAWINGS
[0009] Figure 1 This is a schematic diagram of an atomizer used in the method for producing a powder described in the embodiment.
[0010] Figure 2 This is the phase diagram of copper and chromium.
[0011] Figure 3 This is the phase diagram for iron and copper.
[0012] Figure 4This is a cross-sectional photograph of a sample produced in order to study the powder described in the embodiment.
[0013] Figure 5 It is shown Figure 4 The figure shows a reflected electron image of particles contained in the sample shown.
[0014] Figure 6 It is shown Figure 5 A diagram of the energy spectrum of the particle shown.
[0015] Figure 7 is shown with Figure 5 Figure 2. Reflected electron images of different particles.
[0016] Figure 8 It is a bar graph showing the copper content and the chromium content in each of a plurality of particles.
[0017] Fig. 9 It is shown Figure 8 A bar graph showing the average value of the copper content and the average value of the chromium content.
[0018] Fig.10 It is shown Figure 5 A histogram showing the distribution of the sizes of precipitates in the particles is shown.
[0019] Fig.11 This is a diagram showing a reflected electron image of a cross section of a metal member in Test Example 2.
[0020] Fig.12 It is shown Fig.11 The bar graph shown is a distribution of the sizes of islands in a metal component.
[0021] Fig.13 This is a diagram showing a reflected electron image of a cross section of a metal member in Test Example 3.
[0022] Fig.14 It is shown Fig.13 The bar graph shown is a distribution of the sizes of islands in a metal component.
[0023] Fig.15 This is a diagram showing a reflected electron image of a cross section of a metal member in Test Example 4.
[0024] Fig.16 It is shown Fig.15 The bar graph shown is a distribution of the sizes of islands in a metal component.
[0025] Fig.17 This is a schematic diagram of a vacuum circuit breaker described in the embodiment. DETAILED DESCRIPTION
[0026] [Technical Problems to be Solved by the Present Disclosure]
[0027] According to the purpose of the electric contact material, it is desired that the electric contact material contains a large amount of chromium. However, it is difficult to make an electric contact material with a high chromium content and excellent electrical properties. This is because the quality of the powder used to make the electric contact material is prone to deviation. In the phase diagram of copper and chromium, the more chromium content, the higher the temperature used to reach the liquid phase. If the chromium content increases, it will exceed the heat resistance temperature of the crucible, so the mixture of copper and chromium cannot be made into a liquid phase. In the molten liquid of the mixture heated at a temperature lower than the heat resistance temperature of the crucible, part of the chromium exists as a solid. In the particles obtained by atomizing the molten liquid, the chromium precipitate is easy to coarsen. The deviation of the particle size of the coarsened precipitate is large, and the quality of each particle of the powder is prone to deviation. The quality of the electric contact material obtained by sintering the powder is also prone to deviation. Such a problem may also exist in combinations other than the combination of copper and chromium.
[0028] One of the objects of the present disclosure is to provide a powder which is an aggregate of particles having fine precipitates uniformly dispersed in a matrix and a method for producing the powder. Another object of the present disclosure is to provide a metal component having fine islands uniformly dispersed in a matrix and a method for producing the metal component. Still another object of the present disclosure is to provide an electrical contact formed by the metal component of the present disclosure.
[0029] [Description of Embodiments of the Present Disclosure]
[0030] First, embodiments of the present disclosure will be described by way of examples.
[0031] <1> The powder involved in the embodiment is an aggregate of multiple particles containing a metal element, each of the multiple particles has a matrix and multiple precipitates dispersed in the matrix, the matrix contains a first component, and the multiple precipitates respectively contain a second component, the standard error of the content of the first component in the multiple particles is less than 1.2 based on the mass standard, and the standard error of the content of the second component in the multiple particles is less than 1.2 based on the mass standard.
[0032] The standard error of the content of the first component is calculated as follows. First, a sample in which powder is dispersed in a resin is prepared and the sample is cut. A specified number of particles are extracted from the cross section of the sample, and the content of the first component in each particle is measured. In other words, the contents of multiple first components corresponding to each particle are obtained. The standard error calculated based on the contents of multiple first components is the above-mentioned "standard error of the content of the first component in the multiple particles". The standard error of the content of the second component is also calculated in the same way as the standard error of the content of the first component. The regulation of the standard error of the content of the first component and the second component is one of the indicators indicating that the dispersion state of the precipitates in each particle is similar. In other words, the regulation of the above-mentioned standard error indicates that the quality of each particle constituting the powder is consistent.
[0033] The powder involved in the embodiment is an aggregate of a plurality of particles having a small average particle size, and the quality of each particle is also uniform. The powder having such characteristics improves the quality of a powder compact obtained by pressure molding the powder and the quality of a metal part obtained by sintering the powder compact. In addition, the powder having such characteristics improves the quality of a metal part obtained by metal lamination molding using the powder.
[0034] Here, the precipitate may also be formed in a dendrite shape. In this specification, when evaluating the precipitate, the cross section of the particle is observed. In the case of a dendrite-shaped precipitate, a precipitate that looks like a particle in a specific cross section may be a morphology that is three-dimensionally connected to a precipitate that looks like a particle in other cross sections.
[0035] <2> In the above <1> Among the powders described,
[0036] The standard deviation of the average particle size of the plurality of precipitates in the plurality of particles may be 0.1 or less.
[0037] The standard error of the average particle size of the plurality of precipitates is calculated as follows. First, a predetermined number of particles are extracted from a cross section of a sample in which powder is dispersed in a resin, and the average particle size of the plurality of precipitates contained in each particle is measured. In other words, a plurality of average particle sizes corresponding to each particle are obtained. The standard error calculated based on the plurality of average particle sizes is the above-mentioned "standard error of the average particle size of the plurality of precipitates in the plurality of particles". <2> The standard deviation of the average particle size shown is one of the indicators that the dispersion state of the precipitates in each particle is similar. The powder having such characteristics improves the quality of the pressed powder molded body obtained by pressure molding the powder and the quality of the sintered body obtained by sintering the pressed powder molded body. In addition, the powder having such characteristics improves the quality of the metal parts obtained by metal lamination molding using the powder.
[0038] <3> In the above <1> or <2> Among the powders described,
[0039] The first component and the second component may be a combination having a two liquid phases separate region in a phase diagram, and the content ratio of the first component to the second component may be a content ratio corresponding to the two liquid phases separate region.
[0040] The content ratio of the first component to the second component is the ratio of the content of the first component to the content of the second component when the total content of the first component and the second component is 100% by mass. When the content ratio of the first component to the second component is a content ratio corresponding to the two-liquid phase separation region, the quality of each particle constituting the powder is easy to be consistent.
[0041] <4> In the above <1> to <3> In the powder described in any one of the items,
[0042] The average particle size of the plurality of particles may be 200 μm or less.
[0043] A dense powder compact can be easily obtained by using a powder having an average particle size of 200 μm or less. This is because when a powder having a small average particle size is compacted by pressure, the gaps between particles are easily reduced.
[0044] <5> In the above <1> to <4> In the powder described in any one of the items,
[0045] The average particle size of the plurality of precipitates may be 5 μm or less.
[0046] Above <5> The average particle size is one of the indicators indicating that the precipitates are finely dispersed in each particle. A powder having such characteristics improves the quality of a powder compact obtained by pressure-molding the powder and the quality of a sintered body obtained by sintering the powder compact.
[0047] <6> In the above <1> to <5> In the powder described in any one of the items,
[0048] The maximum particle size of the plurality of precipitates may be 20 μm or less.
[0049] Above <5> The maximum particle size is one of the indicators indicating that the precipitates are finely dispersed in each particle. A powder having such characteristics improves the quality of a powder compact obtained by pressure-molding the powder and the quality of a sintered body obtained by sintering the powder compact.
[0050] <7> In the above <1> to <6> In the powder described in any one of the items,
[0051] The first component may be copper, and the second component may be chromium.
[0052] A powder whose first component is copper and whose second component is chromium, i.e., a powder which is a collection of particles in which chromium precipitates are dispersed in a copper matrix, is suitable as a material for electric contacts. In an electric contact with a high chromium content, the discharge arc tends to disappear in a short time. Thus, the performance of the vacuum circuit breaker is improved.
[0053] The powder whose first component is copper and whose second component is chromium is suitable for the material of the electric contact in the circuit breaker, for example. The higher the chromium content in the powder, the easier it is to improve the performance of the circuit breaker. The chromium content in the powder is, for example, 40% by mass or more. The chromium content in the powder is the proportion of chromium when the total content of copper and chromium contained in the powder is 100% by mass.
[0054] <8> The metal component according to the embodiment is a metal component containing a metal element and includes a base portion and a plurality of island portions dispersed in the base portion, wherein the base portion contains a first component, the plurality of island portions each contain a second component, and the plurality of island portions have an average grain size of 10 μm or less.
[0055] The average particle size of the multiple islands is calculated as follows. First, a predetermined number of observation fields are extracted from the cross section of the metal component, and the particle sizes of all the islands in each observation field are measured. The average particle size of all the islands is the above-mentioned "average particle size of the multiple islands". The metal component having the above-mentioned structure has uniform electrical properties as a whole.
[0056] <9> In the above <8> Among the metal parts described,
[0057] The standard error of the average particle size of the plurality of island portions in a plurality of different observation fields may be 0.3 or less.
[0058] The average particle size of the multiple islands is calculated as follows. First, a specified number of observation fields are extracted from the cross section of the metal component, and the average particle size of the multiple islands in each observation field is measured. In other words, multiple average particle sizes corresponding to each observation field are obtained. The standard error calculated based on the multiple average particle sizes is the above-mentioned "standard error of the average particle size of the multiple islands in different multiple observation fields". The metal component having the above-mentioned structure has uniform electrical properties as a whole.
[0059] <10> In the above <8> or <9> Among the metal parts described,
[0060] The first component and the second component may be a combination having a two-liquid phase separation region in a phase diagram.
[0061] The metal component is produced, for example, from the powder according to the embodiment. The powder according to the embodiment is press-formed to obtain a compact. The metal component is obtained by sintering the compact. <10> The described metal member has characteristics according to the combination of the first component and the second component.
[0062] <11> In the above <8> to <10> In the metal component described in any one of the items,
[0063] The first component may be copper, and the second component may be chromium.
[0064] The metal component whose first component is copper and whose second component is chromium is suitable as the material of the electric contact in the vacuum circuit breaker, for example. In the electric contact with high chromium content, the discharge arc is easy to extinguish in a short time. Therefore, the performance of the vacuum circuit breaker is improved.
[0065] <12> In the above <8> to <11> In the metal component described in any one of the items,
[0066] The content ratio of the first component to the second component may be a content ratio corresponding to a two-liquid phase separation region in a phase diagram.
[0067] If the metal part is made of the powder according to the embodiment, the content ratio of the first component to the second component in the metal part becomes a content ratio corresponding to the two-liquid phase separation region. <12> The described metal member has characteristics according to the content ratio of the first component and the second component.
[0068] Here, when manufacturing the metal part according to the embodiment, if the raw material powder contains other powders in addition to the powder according to the embodiment, the content ratio of the first component to the second component in the metal part may change. For example, if the raw material powder contains copper powder in addition to the powder according to the embodiment in which the first component is copper and the second component is chromium, the content ratio of the first component to the second component in the metal part becomes lower than the content ratio corresponding to the two-liquid phase separation region.
[0069] <13> The electrical contacts according to the embodiment are <8> to <12> It is composed of the metal parts described in any one of the items.
[0070] The electric contact according to the embodiment is formed of a metal member having uniform electrical characteristics as a whole. Therefore, the electric contact according to the embodiment can suppress malfunctions such as malfunctions.
[0071] <14> The method for manufacturing a powder according to the embodiment comprises: step A, preparing a raw material component including a first component and a second component; step B, melting the raw material component by a high-frequency induction heating device without a crucible; and step C, forming a powder from the molten liquid obtained in step B by an atomization method.
[0072] The raw material component is a component obtained by substantially uniformly containing the first component and the second component. The raw material component may be composed of a single type of solid or a plurality of solids combined into one. The high-frequency induction heating device without a crucible can heat the raw material component to a temperature above the heat-resistant temperature of the crucible. By not using a crucible, contamination from the crucible can be prevented.
[0073] The high-frequency induction heating device can heat the raw material parts in a short time. Therefore, the atomization process of step C can be performed before the first component and the second component in the molten liquid are separated into macroscopic two liquids. In addition, since the molten liquid is stirred by the magnetic field generated by the high-frequency induction heating device, the molten liquid of the second component is finely dispersed in the molten liquid of the first component in the molten liquid supplied to the atomization process. Therefore, it is easy to obtain a powder composed of multiple particles with uniform quality.
[0074] <15> In the above <14> In one embodiment of the method for producing the powder,
[0075] The material component may be a powder compact including a first solid in a powder state containing the first component as a main component and a second solid in a powder state containing the second component as a main component.
[0076] In the raw material component composed of the powdered first solid and the powdered second solid, the first component and the second component are uniformly present in the entire raw material component. Therefore, the content ratio of the first component to the second component in the melt obtained by melting the raw material component is easy to become uniform. Therefore, the content ratio of the first component to the second component in the particles constituting the powder is also easy to become uniform.
[0077] <16> In the above <14> or <15> In one embodiment of the method for producing the powder,
[0078] It may also be that the first component and the second component are a combination having a two-liquid phase separation region in the phase diagram, the content ratio of the first component to the second component in the raw material part is a content ratio corresponding to the two-liquid phase separation region, and the temperature of the molten liquid is above the temperature of the two-liquid phase separation region in the phase diagram.
[0079] In the two-liquid phase separation region in the phase diagram, both the first component and the second component exist as liquids. The magnetic field of the high-frequency induction heating device causes the molten liquid of the second component to be finely dispersed in the molten liquid of the first component. Therefore, it is easy to obtain a powder composed of multiple particles with uniform quality.
[0080] <17> In the above <14> to <16> In the method for producing a powder according to any one of the above,
[0081] The first component may be copper, and the second component may be chromium.
[0082] The powder whose first component is copper and whose second component is chromium is suitable for the material of the electrical contacts in the circuit breaker, for example. The higher the chromium content in the powder, the easier it is to improve the performance of the circuit breaker.
[0083] When the content ratio of copper to chromium is a content ratio corresponding to the two-liquid phase separation region in the phase diagram, the content of chromium in the total content of copper and chromium is 47 mass % or more and 80 mass % or less. In this case, a powder with a high chromium content is obtained. The powder with a high chromium content is particularly suitable as an electrical contact material for a circuit breaker.
[0084] <18> The method for manufacturing a metal component according to the embodiment comprises: <1> to <7> The powder according to any one of the above is compacted by pressure to produce a powder compact, and the powder compact is sintered to produce a metal part.
[0085] The powder used in the above-mentioned method for manufacturing a metal component is an aggregate of powders having uniform quality. Therefore, according to the above-mentioned method for manufacturing a metal component, a metal component having uniform electrical characteristics as a whole can be manufactured.
[0086] <19> A method for manufacturing a metal component according to another embodiment is to use the above <1> to <7> A metal component is produced by metal layering of the powder described in any one of the items.
[0087] The powder used in the above-mentioned method for manufacturing a metal component is an aggregate of powders having uniform quality. Therefore, according to the above-mentioned method for manufacturing a metal component, a metal component having uniform electrical characteristics as a whole can be manufactured.
[0088] [Description of Embodiments of the Present Disclosure]
[0089] The following describes implementation aspects of the present disclosure.
[0090] [Details of the embodiments of the present disclosure]
[0091] Hereinafter, specific examples of the method for manufacturing the powder, the powder, the metal parts and the electrical contacts disclosed in the present invention will be described based on the accompanying drawings. In the following, the same reference numerals in the figures represent the same or equivalent parts. The sizes of the parts shown in the drawings are presented for the purpose of clear description and do not necessarily represent the actual sizes. It should be noted that the present invention is not limited to these examples, but is shown by the claims, and is intended to include all changes within the meaning and scope equivalent to the claims.
[0092] <Implementation Method 1>
[0093] 《Method for producing powder》
[0094] exist Figure 1 , an atomizer 1 is shown as an example of an apparatus for implementing the method for producing a powder described in the embodiment. The atomizer 1 includes a housing 10 , a partition 11 , a pressing device 12 , a high-frequency induction heating device 13 , a nozzle 14 , and a recovery tank 15 .
[0095] The housing 10 separates the working environment from the external environment. The partition 11 is arranged in the middle of the height direction of the housing 10 to divide the internal space of the housing 10. In the space above the partition 11, the raw material component 2 is melted. Therefore, the space above becomes high temperature. The molten liquid 20 of the raw material component 2 falls from the hole of the partition 11 to the space below the partition 11. In the space below the partition 11, the molten liquid 20 is atomized by the atomization method. The inside of the housing 10 is, for example, an inactive atmosphere.
[0096] The pressing device 12 supplies the long raw material component 2 to the high-frequency induction heating device 13. The figure shows only the rod 12r that is configured to be movable in the up-down direction in the pressing device 12. The raw material component 2 is fixed to the front end of the rod 12r. The rod 12r moves downward according to the molten state of the raw material component 2, thereby continuously supplying a predetermined amount of the raw material component 2 to the high-frequency induction heating device 13.
[0097] The high-frequency induction heating device 13 does not have a crucible. The high-frequency induction heating device 13 includes, for example, a coil 13c, a power line for supplying high-frequency power to the coil 13c, and a control unit for adjusting the amount of power supplied to the coil 13c. Only the coil 13c is shown in the figure. The magnetic field generated by the coil 13c melts the raw material component 2 into a molten liquid 20 by induction heating, and stirs the molten liquid 20.
[0098] The nozzle 14 sprays a fluid such as gas or water into the space below the partition 11. The molten liquid 20 scattered by the gas or water is cooled and becomes particles 4. The particles 4 are stored in a recovery tank 15 arranged at the bottom of the housing 10. The powder 3, which is an aggregate of a plurality of particles 4 stored at the bottom of the recovery tank 15, can also be recovered by, for example, a cyclone recovery machine. Fine particles 4 with a predetermined particle size or less are recovered by the cyclone recovery machine. Coarse particles 4 remain in the recovery tank 15. The powder 3 can also be sieved.
[0099] The method for producing the powder of this example comprises the following steps. Figure 1 A method for manufacturing a powder of an atomizer 1 will be described.
[0100] Step A: a step of preparing a raw material member 2 including a first component and a second component.
[0101] Step B: A step of melting the raw material component 2 using a high-frequency induction heating device 13 that does not have a crucible.
[0102] Step C: a step of converting the melt 20 obtained in step B into powder 3 by atomization.
[0103] Hereinafter, each step will be described in detail.
[0104] [Process A]
[0105] The first component and the second component in the raw material part 2 are, for example, a combination having a two-liquid phase separation region in a phase diagram. The first component and the second component are respectively a metal element or a compound of a metal element. In this specification, the metal element includes silicon (Si). The first component forms a matrix in the particle 4. The second component forms a precipitate dispersed in the matrix in the particle 4. The raw material part 2 may also contain inevitable impurities.
[0106] The raw material component 2 may also be composed of a first solid having the first component as a main component and a second solid having the second component as a main component. In this case, the first component may be contained only in the first solid or in the first solid and the second solid. Similarly, the second component may be contained only in the second solid or in the first solid and the second solid. The raw material component 2 may also include at least one other solid having a composition different from that of the first solid and the second solid.
[0107] The raw material component 2 is, for example, a powder compact obtained by compressing raw material powders including a powdered first solid and a powdered second solid. The average particle size of the raw material powder is, for example, greater than 1 μm and less than 150 μm. Raw material powders with an average particle size of greater than 1 μm are excellent in productivity, including operability and cost. Raw material powders with a small average particle size are labor-intensive to produce. Raw material powders with an average particle size of less than 150 μm can suppress the deviation of the content ratio in each part of the raw material component 2. For this reason, the quality of the powder 3 produced using the raw material component 2 is uniform. The average particle size of the raw material powder can also be greater than 20 μm and less than 75 μm. The average particle size of the raw material powder can be measured using a particle size distribution analyzer. In this example, the average particle size is D50, which is a mass standard.
[0108] The raw material component 2 may be, for example, a component formed by bundling a linear first solid and a linear second solid, or a component formed by twisting them. The cross-sectional shape of the first solid and the second solid may be circular, polygonal, or star-shaped. The cross-sectional area of a line of the first solid in a cut plane perpendicular to the length direction of the first solid is, for example, 1 mm 2 Above and 7mm 2 The cross-sectional area of a line of the second solid in a cut plane perpendicular to the longitudinal direction of the second solid is, for example, 1 mm 2 Above and 7mm 2 Below. Cross-sectional area is 1mm 2 The first solid and the second solid are excellent in productivity including cost. It takes time to make a wire with a small cross-sectional area. The cross-sectional area of one wire is 7 mm 2 The first solid and the second solid below can suppress the deviation of the content ratio of the first component and the second component in each portion in the length direction of the raw material part 2. Therefore, the quality of the powder 3 produced using the raw material part 2 is uniform. The cross-sectional area of a line of the first solid and the second solid can be 2mm 2 Above and 4mm 2 Below, can also be 2mm 2 Above and 3mm 2 the following.
[0109] In addition, the raw material component 2 can also be manufactured by an infiltration method in which a molten liquid is filled into a porous material. In this case, for example, the porous material may be composed of the first component and the molten liquid may be composed of the second component. In addition, the material containing the first component and the second component may be heated to a liquid phase region by an arc melting method or the like in a water-cooled copper hearth, etc., and then rapidly cooled to manufacture an ingot-shaped raw material component 2. The liquid phase region is a region in which the first component and the second component are not separated but exist as one liquid phase.
[0110] The two-liquid phase separation region in the phase diagram refers to a region where the molten liquid of the first component and the molten liquid of the second component exist in a separated state. The temperature of the two-liquid phase separation region is generally lower than the temperature of the liquid phase region.
[0111] The phase diagram can be a phase diagram of a binary system or a phase diagram of a multi-component system. The first component and the second component are composed of different materials. The melting point of the first component is different from the melting point of the second component. The combination of the first component and the second component is, for example, a metal element-metal element, a metal element-a compound of a metal element and a non-metal element, or a compound of a metal element and a non-metal element-a compound of a metal element and a non-metal element. Specific combinations of the first component and the second component are, for example, silver (Ag)-manganese (Mn), Ag-nickel (Ni), aluminum (Al)-bismuth (Bi), Al-indium (In), Bi-gallium (Ga), Bi-zinc (Zn), copper (Cu)-chromium (Cr), Cu-niobium (Nb), iron (Fe)-Cu, Fe-In, Fe-tin (Sn), lithium (Li)-LiH, Ag-AgO, barium (Ba)-BaO, Bi-BiO, cobalt (Co)-Co3O4, Cr-Cr2O3, Cu-Cu2O, Fe-FeO, Ni-NiO, Sn-SnO, Zr-ZrO, and Fe2O3-SiO2. In the above combination, the first component is recorded on the left side of "-", and the second component is recorded on the right side of "-". The above combination also includes a combination in which an alloy that shows miscibility in a liquid state, such as Fe-Cu, becomes a two-liquid phase separation state in a supercooled state or in the presence of impurities.
[0112] Figure 2 and Figure 3 An example of a phase diagram is shown in FIG. Figure 2 It is the phase diagram of Cu-Cr. Figure 2 The horizontal axis is the content of Cr in the Cu-Cr alloy. The unit of the lower horizontal axis is atomic %, and the unit of the upper horizontal axis is mass %. Figure 2 The vertical axis is temperature. The unit of temperature is °C. "L" in the figure is the liquid phase region, and "L1+L2" is the two liquid phase separation region. Figure 3 It is the phase diagram of Fe-Cu. Figure 3 The horizontal axis is the molar ratio of Cu in the Fe-Cu alloy, and the vertical axis is the temperature. The unit of temperature is Kelvin. Figure 3 In the figure, the area surrounded by the horizontal line of 1361K and the thick dotted line is the two-liquid phase separation area. For example, by increasing the content ratio of trace elements such as carbon and oxygen in Fe-Cu, Fe and Cu are easily separated into two liquid phases, and the combination of components formed by adjusting such trace elements is also within the scope of the present invention. For reasons such as helping to improve the characteristics of the product, the raw material component 2 may also contain other elements within the range that does not affect or hinder the formation of the two-liquid phase region.
[0113] The content ratio of the first component to the second component in the raw material part 2 is a content ratio corresponding to the two-liquid phase separation region in the phase diagram. Figure 2 In the Cu-Cr phase diagram shown, when the total content of Cu and Cr contained in the raw material component is set to 100 mass%, the content of Cr in the total content is 47 mass% or more and 80 mass% or less. The raw material component 2 containing 47 mass% or more and 80 mass% or less of Cr may become a two-liquid phase separation state as the temperature of the raw material component 2 rises.
[0114] [Process B]
[0115] In step B, the raw material component 2 is melted by a high-frequency induction heating device 13 without a crucible. The temperature of the two-liquid phase separation region is lower than the temperature of the liquid phase region. Since the molten liquid 20 cannot be stored in advance in the high-frequency induction heating device without a crucible, it is difficult to heat the molten liquid to the temperature of the liquid phase region.
[0116] The magnetic field generated by the high-frequency induction heating device 13 violently stirs the molten liquid 20. Even if the molten liquid 20 is a two-liquid phase separation state of the molten liquid of the first component and the molten liquid of the second component, the molten liquid of the first component and the molten liquid of the second component will be violently stirred. Through this stirring, the molten liquid of the second component is finely dispersed in the molten liquid of the first component. At this time, since the molten liquid 20 is completely liquefied, the first solid can be an alloy containing both the first component and the second component, or the second solid can be an alloy containing both the first component and the second component. The frequency of the current that makes the high-frequency induction heating device 13 work is, for example, above 100kHz. The high-frequency current above 100kHz causes the temperature of the coil 13c to rise rapidly. In addition, the high-frequency current above 100kHz enables the molten liquid of the first component and the molten liquid of the second component to be fully stirred. The above frequency can be above 125kHz or above 150kHz.
[0117] [Process C]
[0118] In step C, the molten liquid 20 is made into powder 3 by atomization. In the atomization method, a fluid such as gas or water is sprayed from the nozzle 14 toward the molten liquid 20. The molten liquid 20 is scattered by the gas or water, and the scattered molten liquid 20 is rapidly solidified. As a result, a powder 3 composed of fine particles 4 is obtained. The gas is, for example, argon, helium or nitrogen. The particle size of the particle 4 changes depending on the pressure of the gas. In addition, depending on the type of fluid, the cooling rate of the particle 4 changes, and the internal structure of the particle 4 changes. In particular, the difference in cooling capacity between the gas phase gas and the liquid phase water is large.
[0119] "powder"
[0120] The average particle size of the powder 3 produced by the above-mentioned powder manufacturing method, that is, the average particle size of the plurality of particles 4, is, for example, 200 μm or less. By press-molding the powder having an average particle size of 200 μm or less, a dense pressed powder molded body with few voids can be produced. The average particle size of the powder 3 is obtained by image analysis using a SEM (Scanning Electron Microscope). The average particle size of the particles 4 may be 100 μm or less, 50 μm or less, or 10 μm or less. The lower limit of the average particle size of the particles 4 is, for example, 1 μm or more.
[0121] Figure 4 This is a SEM image of a cross section of a sample 6 produced in the test example 1 described below. Sample 6 is produced by grouping powder 3 with resin 5. In this specification, the equivalent circle diameter of a particle 4 in an SEM image is the particle size of the particle 4. The equivalent circle diameter is calculated as follows. First, the SEM image is binarized to calculate the area of each particle 4 in the field of view. The diameter of a circle of the same size as the area of each particle 4 is the equivalent circle diameter. The value obtained by averaging the equivalent circle diameters of all particles 4 in the field of view is the average particle size of the powder 3.
[0122] based on Figure 5 The structure of each particle 4 will be described. Figure 5 : is a secondary electron image of the particle 4 produced in Experimental Example 1 described below. The secondary electron image was obtained by SEM-EDX (Energy Dispersive X-ray Spectroscopy). Figure 5 As shown, the particle 4 includes a matrix 40 and a plurality of precipitates 41 dispersed in the matrix 40. The matrix 40 is composed mainly of the first component, and the precipitates 41 are composed mainly of the second component. Figure 5 The matrix 40 in the embodiment is copper, and the precipitate 41 is chromium.
[0123] The content ratio of the first component to the second component in the particle 4 corresponds to the two-liquid phase region in the phase diagram. It is considered that the content ratio in the particle 4 maintains the content ratio in the raw material component 2 prepared in the powder production method.
[0124] The standard deviation of the content of the first component in the plurality of particles 4 is less than 1.2 on a mass basis. In addition, the standard deviation of the content of the second component in the plurality of particles 4 is also less than 1.2 on a mass basis. These indices indicate that the deviation of the content of the first component and the content of the second component in each particle is small. That is, the powder 3 that meets this index is composed of a plurality of particles 4 having uniform quality.
[0125] The contents of the first component and the second component are obtained by SEM-EDX. First, more than ten particles that can contain an observation field of a specific size are selected from the plurality of particles 4 in the SEM image. The energy spectrum of the characteristic X-ray is obtained from the observation field of each selected particle 4. The contents of the first component and the second component are obtained based on the area of the peak corresponding to the first component and the area of the peak corresponding to the second component in the energy spectrum. In this example, the contents of the first component and the second component are automatically obtained by the Xmax70+Aztec ver.3 software developed by Oxford Instruments.
[0126] The average particle size of the plurality of precipitates 41 in each particle 4 is, for example, 5 μm or less. This provision is one of the indicators indicating that the precipitates 41 are finely dispersed in each particle 4. The powder 3 having such characteristics improves the quality of the powder compact obtained by pressure-molding the powder 3 and the quality of the metal part obtained by sintering the powder compact. The particle size of the precipitate 41 is the equivalent circle diameter of the precipitate 41 obtained from the SEM-EDX image. The average particle size of the plurality of precipitates 41 is the average value of the particle sizes of the plurality of precipitates 41 obtained from a specified number of particles 4 arbitrarily extracted. The above-mentioned specified number is 10 or more. The average particle size of the precipitate 41 may also be, for example, 2 μm or less.
[0127] The standard error of the average particle size of the precipitates 41 in the plurality of particles 4 is, for example, less than 0.1. This provision is one of the indicators indicating that the dispersion states of the precipitates 41 in each particle 4 are similar. That is, the powder 3 satisfying this indicator is composed of a plurality of particles 4 having uniform quality. The particles 4 for which the average particle size is measured are the same as the particles 4 for which the energy spectrum of the reflected electrons is obtained. The average particle size of the precipitates 41 in each particle 4 is the average of the equivalent circle diameters of all precipitates 41 present in the observation field of view within a specified range in each particle 4. The above standard error may also be, for example, less than 0.5.
[0128] The maximum particle size of the plurality of precipitates 41 in the plurality of particles 4 is, for example, 20 μm or less. The maximum particle size of the precipitates 41 in each of the plurality of particles 4 contained in the powder 3 being 20 μm or less is one of the indicators indicating that the precipitates 41 are finely dispersed in each particle 4. The powder 3 having such characteristics improves the quality of the pressed powder compact obtained by pressure-molding the powder 3 and the quality of the sintered body obtained by sintering the pressed powder compact. The particle 4 for which the maximum particle size is measured is the same as the particle 4 for which the energy spectrum of the reflected electron is obtained. The above-mentioned maximum particle size may also be, for example, 15 μm or less.
[0129] Metal Parts
[0130] The metal component of this example is produced using the above-mentioned powder 3 as a raw material, for example. Fig.11This is a secondary electron image of a cross section of a metal member 7 produced in Experimental Example 2 described below. Fig.13 This is a secondary electron image of a cross section of a metal component 7 produced in Experimental Example 3 described below. Fig.11 The structure of the metal member 7 will be described.
[0131] Fig.11 The metal component 7 includes a base portion 70 and a plurality of island portions 71. The plurality of island portions 71 are dispersed in the base portion 70. The base portion 70 is composed of a first component. The island portions 71 are composed of a second component. The first component and the second component are a combination having a two-liquid phase separation region in a phase diagram.
[0132] The islands 71 may be formed in a particle shape or a dendrite shape. In the case of the dendrite-shaped islands 71, the islands 71 that appear to be particle-shaped in a specific cross section may be three-dimensionally connected to the islands 71 that appear to be particle-shaped in other cross sections.
[0133] The average particle size of the plurality of island portions 71 is 10 μm or less. This provision is one of the indicators indicating that the island portions 71 are finely dispersed in the metal component 7. In this specification, the particle size of the island portion 71 is the equivalent circle diameter of the island portion 71 obtained from the SEM-EDX image. The average particle size of the plurality of island portions 71 is the average value of the particle sizes of the plurality of island portions 71 obtained from a predetermined number of observation fields extracted arbitrarily. The predetermined number is 10 or more. The average particle size of the island portion 71 can be, for example, 4 μm or less, or 3.5 μm or less.
[0134] The standard error of the average particle size of the multiple island portions 71 in the metal component 7 is, for example, less than 0.3. This regulation is one of the indicators that the dispersion state of the island portions 71 is similar throughout the entire range of the metal component 7. That is, the metal component 7 that meets this indicator has uniform quality as a whole. The above standard error is calculated as follows. First, extract multiple observation fields of specific size. The size of each observation field of view is, for example, 100μm×100μm. The number of observation fields of view is, for example, ten. The average particle size, that is, the average equivalent circle diameter, of all the island portions 71 in each observation field of view is calculated. Based on the multiple average particle sizes obtained from each observation field of view, the above standard error is calculated. The above standard error can be less than 0.25 or less than 0.15.
[0135] The content ratio of the first component to the second component in the metal component 7 of this example is equal to the content ratio of the first component to the second component in the powder 3. The content ratio in the metal component 7 is obtained by the same method as the content ratio in the powder 3. That is, the content ratio in the metal component 7 is obtained by analyzing the cross section of the metal component 7 by SEM-EDX. For example, when the first component is copper and the second component is chromium, the content of chromium in the metal component 7 is 47% by mass or more and 80% by mass. Here, when the raw material powder of the metal component 7 contains copper powder in addition to the powder 3, the content of chromium in the metal component 7 decreases. In this case, a metal component 7 having a chromium content of 30% by mass or more and less than 47% by mass is obtained. In addition, when the raw material powder of the metal component 7 contains chromium powder in addition to the powder 3, the content of chromium in the metal component 7 increases. In this case, a metal component 7 having a chromium content exceeding 80% by mass is obtained.
[0136] The maximum grain size of the island portion 71 is, for example, 50 μm or less. The metal member 7 having no coarse island portion 71 has uniform quality as a whole. The maximum grain size of the island portion 71 may be, for example, 40 μm or less, or 30 μm or less.
[0137] 《Method for manufacturing metal parts》
[0138] The method for manufacturing the first metal component is to produce a powder compact by press-forming the powder 3, and to produce the metal component 7 by sintering the powder compact. The pressure of the press-forming is, for example, 10 MPa (megapascals) or more and 100 MPa or less. The sintering temperature is, for example, 800° C. or more and 1050° C. or less. The atmosphere during sintering is, for example, a vacuum atmosphere.
[0139] The manufacturing method of the second metal component is to make a metal component 7 by using the metal stacking modeling of the above-mentioned powder 3. The metal stacking modeling device can be a device of a directed energy deposition method or a device of a powder bed method. In the device of the directed energy deposition method, the powder 3 is melted by a laser while being sprayed, and the molten metal is stacked. In the device of the powder bed method, after the powder 3 is fully spread, the powder 3 is irradiated with a laser or an electron beam to melt the powder 3. The average particle size of the powder 3 provided for metal stacking modeling is, for example, greater than 20 μm and less than 100 μm. The powder 3 having such an average particle size is easy to melt, and for this reason, the electrical properties of the metal component 7 are easy to become uniform.
[0140] When the powder 3 contains copper, the powder 3 is easily melted if it is a blue laser. This is because copper easily absorbs the blue laser. The output of the blue laser is, for example, 100 W or more and 300 W or less. The scanning speed of the blue laser is, for example, 5 mm / s or more and 40 mm / s or less.
[0141] 《Method for manufacturing electric contact material》
[0142] The powder 3 is, for example, a material of an electric contact. A device having an electric contact is, for example, a gas circuit breaker or a vacuum circuit breaker. Fig.17 : is a schematic diagram of a vacuum circuit breaker 9. The vacuum circuit breaker 9 includes a vacuum valve 90, a fixed terminal 91, a movable terminal 92, a bellows 93, and an arc shield 94. The inside of the vacuum valve 90 is evacuated. The fixed terminal 91 includes an electrode rod 91A and a fixed contact 91B. The movable terminal 92 includes an electrode rod 92A and a movable contact 92B. The movable terminal 92 is configured to be able to reciprocate along the axial direction of the electrode rod 92A. The bellows 93 expands and contracts as the movable terminal 92 moves, and maintains the vacuum inside the vacuum valve 90. The arc shield 94 shields the arc generated between the fixed contact 91B and the movable contact 92B.
[0143] In the vacuum circuit breaker 9, for example, the fixed contact 91B of the fixed terminal 91 and the movable contact 92B of the movable terminal 92 are made from the powder 3. Specifically, the powder 3 is pressed to form a compact. Then, the electric contact material is made by sintering the compact. The fixed contact 91B and the movable contact 92B are made by shaping the electric contact material. The electric contact material may also be subjected to cutting and the like. In addition, the fixed contact 91B and the movable contact 92B may also be made using a metal stacking molding device such as an electron beam method or a laser melting method. For example, the electrode rods 91A and 92A may be used as the bottom plate during the metal stacking molding, and the fixed contact 91B and the movable contact 92B may be integrated with the electrode rod 91A and the electrode rod 92A, respectively. In this case, the materials and processes required for joining the electrode rod 91A with the fixed contact 91B and the electrode rod 92A with the movable contact 92B are omitted.
[0144] If the content of chromium contained in the fixed contact 91B and the movable contact 92B increases, the arc generated between the fixed contact 91B and the movable contact 92B is easy to disappear. Therefore, the vacuum circuit breaker 9 having the fixed contact 91B and the movable contact 92B composed of a Cu-Cr alloy having a chromium content of 47 mass % or more and 80 mass % or less has excellent circuit breaking performance. In this example, the fixed contact 91B and the movable contact 92B are formed by a structure in which chromium is finely dispersed in a copper matrix. Between the fixed contact 91B and the movable contact 92B having such a structure, the arc is easy to disappear. Therefore, the vacuum circuit breaker 9 of this example has excellent circuit breaking performance. The powder 3 of this example can also be used as a raw material for the bellows 93.
[0145] 《Test Example 1》
[0146] In Test Example 1, using Figure 1The atomizer 1 shown was used to actually produce the powder 3 and to study the structure and the like of the powder 3.
[0147] Raw material component 2 is produced by press-molding copper powder and chromium powder. Copper powder is produced by water atomization method. The average particle size of copper powder is 150μm. Chromium powder is produced by aluminothermic method. The average particle size of chromium powder is 150μm. The average particle size of copper powder and chromium powder is D50 measured by a particle size distribution instrument. D50 is a mass standard. The chromium powder contains aluminum oxide as an inevitable impurity. The content ratio of copper powder to chromium powder in raw material component 2 is the content ratio corresponding to the two-liquid phase separation region in the Cu-Cr phase diagram. Specifically, when the total of copper and chromium in raw material component 2 is set to 100% by mass, the copper content is 50% by mass and the chromium content is 50% by mass.
[0148] The press molding was performed by a cold isostatic press (CIP). The inner dimensions of the rubber mold of the CIP were cylindrical with a diameter of 60 mm and a length of 270 mm. The pressure of the CIP was 390 MPa.
[0149] The raw material component 2 was placed in the atomizer 1, and the high-frequency induction heating device 13 was operated at a frequency of 125 kHz and a current value of 200 mA to melt the raw material component 2. Nitrogen gas was sprayed from the nozzle 14 to scatter the molten liquid 20 dropped from the bottom of the raw material component 2, thereby producing a plurality of particles 4.
[0150] The powder 3 stored in the recovery tank 15 is recovered, and the recovered powder 3 is sieved. The aperture of the sieve is 150 μm.
[0151] Using the above powder 3, Figure 4 The sample 6 shown is made by mixing the resin 5 and the powder 3 and curing the resin 5. Figure 4 This is an SEM image obtained by photographing a cross section of the sample 6 cut using a focused ion beam.
[0152] Through Figure 4 The average particle size of the powder 3 was measured by performing image analysis on the SEM image. Figure 4 The field of view size is 0.5 mm × 0.5 mm. In the image analysis, the SEM image is binarized and all particles 4 in the field of view are extracted. The diameter of a circle of the same size as the area of the particle 4 is calculated. This equivalent circle diameter is regarded as the particle size of the particle 4. The average particle size of the powder 3, that is, the average particle size of the plurality of particles 4, is the average of the equivalent circle diameters of all particles 4 in the field of view. In this example, the number of particles 4 is 150. The average particle size of the powder 3 of the test example is 120 μm.
[0153] Next, the structure of each particle 4 was observed by SEM-EDX. Figure 5 It is a reflected electron image of an arbitrary particle 4. Figure 5 The white part in the figure is the matrix 40 composed of Cu, the gray part is the precipitate 41 composed of Cr, and the black dots are aluminum oxide. Figure 5 As shown, in the particle 4 of this example, a state in which a plurality of fine precipitates 41 are dispersed in the matrix 40 is observed.
[0154] In order to investigate the uniformity of the plurality of particles 4 constituting the powder 3, the copper content and the chromium content in ten random particles 4 were measured. The particles 4 selected for the measurement had a thickness of 400 μm that could be ensured inside the outer periphery of the particles 4. 2 The size of the quadrilateral's observation field of view. Figure 5 The lightly indicated rectangle in the figure is the observation field of view, and the energy spectrum in the observation field of view is acquired. Figure 6 yes Figure 5 The energy spectrum of particle 4 shown in FIG. The horizontal axis is the energy (keV) of the reflected electrons, and the vertical axis is the count rate (cps / eV). The copper content and the chromium content can be obtained from the energy spectrum, but since the diffusion mode of the electron beam is different for each element according to the acceleration voltage of the electron gun of the SEM, the result of this numerical value varies according to the setting value of the acceleration voltage. In principle, it is an indicator for defining the standard error of each particle. This time, the acceleration voltage was set to 5kV, and an energy dispersive characteristic X-ray analyzer (EDX) was used. At this time, the electron gun and the detection element were set to obtain a sufficient S / N ratio. According to the size of the detection element used, the setting was made so that the dead time was about 10% to 20%. This time, JSM-7600F manufactured by JEOL was used, and the aperture of the objective lens was 4, the irradiation current was 1nA, and the processing time was 5. The content ratio of the first component to the second component in the entire powder 3 was obtained by an ICP emission spectrometer of ICPS-8100 manufactured by Shimadzu Corporation. The analysis value of the powder 3 produced in this example was chromium: 50.6 mass %.
[0155] Figure 7 is with Figure 5 Reflected electron images of different particles 4. Figure 7 The size and dispersion state of the precipitate 41 in the particle 4 shown are similar to Figure 5 The particles 4 shown are substantially the same. Although not shown in the drawings in this specification, the reflected electron images of the ten particles 4 have very similar appearances.
[0156] Figure 8 It is a bar graph showing the copper content and the chromium content in each of the ten particles 4. The horizontal axis is the sample No., and the vertical axis is mass %. The columns with 45° hatching are the copper content, and the columns with 135° hatching are the chromium content. Fig. 9is a bar graph showing the average copper content and the average chromium content. The error bars in the graph represent standard errors. In this example, the standard error of the average copper content is 1.1. In addition, the standard error of chromium is also 1.1. Figure 8 and Fig. 9 The results show that the deviation between the copper content and the chromium content in each particle 4 is very small.
[0157] Next, the particle size of each of the plurality of precipitates 41 included in the particle 4 was measured. Fig.10 It is a summary Figure 5 Graph showing the measurement results of the equivalent circle diameter of each precipitate 41 of the particle 4. In this example, the equivalent circle diameter of the precipitate 41 is regarded as the particle size of the precipitate 41. The measurement objects having an equivalent circle diameter of 0.39 μm or less are not counted as precipitates 41. Fig.10 The horizontal axis is the equivalent circle diameter, and the vertical axis is the relative frequency based on the number. The unit of the equivalent circle diameter is μm. The column located at the position where the equivalent circle diameter is an integer k is the column obtained by summing the number of precipitates 41 whose equivalent circle diameter is greater than or equal to kμm and less than k+0.5μm. For example, the column located at the position where the equivalent circle diameter is 0μm is the column obtained by summing the number of precipitates 41 whose equivalent circle diameter is greater than or equal to 0 and less than 0.5μm. The column whose equivalent circle diameter is between the integer k and the integer k+1 is the column obtained by summing the number of precipitates 41 whose equivalent circle diameter is greater than or equal to k+0.5μm and less than or equal to kμm. For example, the column whose equivalent circle diameter is between 0μm and 1μm is the column obtained by summing the number of precipitates 41 whose equivalent circle diameter is greater than or equal to 0.5μm and less than or equal to 1.0μm.
[0158] In this manual, although not shown in the figure, Figure 5 Nine particles 4 other than the particle 4 shown also obtained the same Fig.10 The average particle size and the maximum particle size of the precipitates 41 in each of the ten particles 4 are shown in Table 1. In the ten particles 4, no precipitates 41 larger than 20 μm were confirmed.
[0159] [Table 1]
[0160]
[0161] The "average particle size of the precipitate" in Table 1 is the average value of the precipitate 41 contained in each particle 4. "Average" is the average value of ten average particle sizes, that is, the average particle size of the precipitate 41 in the entire powder 3. The standard deviation of the ten average particle sizes is 0.19, and the standard error is 0.06. The standard error of the average particle size of the precipitate 41 in the plurality of particles 4 is 0.1. The following is one of the indicators indicating that the dispersion state of the precipitate 41 in each particle 4 is similar. The powder 3 having such characteristics improves the quality of the powder compact obtained by pressure-molding the powder 3 and the quality of the metal component 7 obtained by sintering the powder compact.
[0162] 《Test Example 2》
[0163] In Test Example 2, a metal component 7 was produced from the powder 3 of Test Example 1, and the structure of the metal component 7 was studied.
[0164] First, a powder compact was produced by press-molding the powder 3. The press-molding was performed by a hydraulic press. The surface pressure of the hydraulic press was 20 tons / cm 2 (1961 MPa). The powder compact was in the shape of a cylinder with a diameter of 30 mm. Next, the powder compact was vacuum sintered at 900° C. to produce a metal component 7.
[0165] The cross section of the produced metal member 7 was photographed by SEM, and the structure of the cross section of the metal member 7 was observed. The cross section was polished with colloidal silica. The number of observation fields was 10. The size of the observation field was 100 μm×100 μm. Fig.11 It is a reflected electron image of one of the ten observation fields. The reflected electron images of the ten observation fields are similar. The acquisition conditions of the reflected electron image are the same as those of Experimental Example 1. Fig.11 The magnification is 3000 times. Fig.11 The image is part of the observation field of view and is narrower than the observation field of view.
[0166] The particle size, that is, the equivalent circle diameter, of the island portion 71 was measured from the reflected electron image of the cross section. The method for measuring the equivalent circle diameter of the island portion 71 was the same as the method for measuring the precipitate 41 in Test Example 1. The measurement objects having an equivalent circle diameter of 0.28 μm or less were not counted as the island portion 71. Fig.12 It is a summary Fig.11 The graph of the measurement results of the equivalent circle diameter of the island portion 71 in the observation field shown in FIG. Fig.12 Methods and Fig.10 The average particle size and the maximum particle size of the island portion 71 obtained from each of the ten observation fields are shown in Table 2. The method of viewing Table 2 is the same as that of Table 1.
[0167] [Table 2]
[0168]
[0169] The "average" in Table 2, that is, the average particle size of all the island portions 71 contained in the metal component 7, is 3.35 μm. The average particle size of the island portions 71 is 10 μm or less, which is one of the indicators indicating that the island portions 71 are finely dispersed in the base portion 70. In addition, the standard deviation of the average particle size of ten observation fields is 0.65, and the standard error is 0.21. The standard error is 0.3 or less, which is one of the indicators indicating that the dispersion state of the island portions 71 is similar throughout the entire range of the metal component 7. Furthermore, the maximum particle size of the island portion 71 is 45.26 μm. The maximum particle size is 50 μm or less, which is one of the indicators indicating that the metal component 7 has uniform quality as a whole. Therefore, it is clear that the metal component 7 shown in Test Example 2 has uniform quality as a whole.
[0170] 《Test Example 3》
[0171] In Test Example 3, a metal component 7 different from that in Test Example 2 was produced, and the structure of the metal component 7 was examined. The only difference between Test Example 3 and Test Example 2 was that the vacuum sintering temperature was 1000°C.
[0172] Fig.13 This is a reflected electron image of one observation field in the cross section of the metal member 7 in this example. Fig.13 The magnification is 3000 times. Fig.14 It is a summary Fig.13 3 is a graph showing the measurement results of the equivalent circle diameter of the island portion 71 in the observation field shown in FIG. 1. In this example, ten different observation fields were studied. The average particle size and the maximum particle size of the island portion 71 obtained from each of the ten observation fields are shown in Table 3.
[0173] [Table 3]
[0174]
[0175] The “average” in Table 3, that is, the average grain size of all islands 71 included in the metal member 7, is 3.74 μm. The standard deviation and standard error are 0.41 and 0.13, respectively. Therefore, it is clear that the metal member 7 shown in Test Example 3 also has uniform quality as a whole.
[0176] The average particle size of all islands 71 in Test Example 3 is slightly larger than the average particle size of all islands 71 in Test Example 2. In addition, the average value of the maximum particle size in ten observation fields in Test Example 3 is also slightly larger than the average value of the maximum particle size in ten observation fields in Test Example 2. The only difference between Test Example 3 and Test Example 2 is the temperature of vacuum sintering. Therefore, it can be seen that the islands 71 tend to become coarser as the temperature of vacuum sintering increases.
[0177] 《Test Example 4》
[0178] In Test Example 4, a metal component 7 was produced by metal layered molding using the powder 3 of Test Example 1, and the structure of the metal component 7 was examined.
[0179] The metal lamination molding device is ALPION Type Blue manufactured by Muratani Machinery Co., Ltd. The metal lamination molding device performs molding by irradiating three blue lasers while spraying powder 3. The maximum output of each blue laser is 100 W and the wavelength is 445 nm.
[0180] The conditions for the metal lamination molding in this example are as follows.
[0181] · Average particle size of powder 3…80 μm
[0182] ·Spraying amount of powder 3: 10 g / min
[0183] ·Blue laser output…100W
[0184] ·Blue laser scanning speed…40mm / s
[0185] The cross section of the manufactured metal member 7 was observed by the same method as in Test Examples 2 and 3. Fig.15 This is a reflected electron image of the observation field in the cross section of the metal member 7 in this example. Fig.15 The magnification is 1000 times. Fig.16 It is a summary of Fig.15 The graph of the measurement results of the equivalent circle diameter of the island portion 71 obtained from the observation field shown in FIG. 1 is a graph of the measurement results of the equivalent circle diameter of the island portion 71 obtained from the observation field shown in FIG. 1. In this example, ten different observation fields are studied. The average particle size and the maximum particle size of the island portion 71 obtained from each of the ten observation fields are shown in Table 4.
[0186] [Table 4]
[0187]
[0188] The "average" in Table 4, that is, the average particle size of all the island portions 71 contained in the metal component 7 is 1.14μm. The average particle size of the island portions 71 is 10μm or less, which is one of the indicators indicating that the island portions 71 are finely dispersed in the base portion 70. In addition, the standard deviation of the average particle size of ten observation fields is 0.09, and the standard error is 0.03. The standard error is 0.3 or less, which is one of the indicators indicating that the dispersion state of the island portions 71 is similar throughout the entire range of the metal component 7. Furthermore, the maximum particle size of the island portion 71 is 41.62μm. The maximum particle size is 50μm or less, which is one of the indicators indicating that the metal component 7 has uniform quality as a whole. Therefore, it is clear that the metal component 7 shown in Test Example 4 has uniform quality as a whole.
[0189] like Fig.15As shown in the photo of FIG. 1 , in metal lamination molding, an enriched layer 75 with more islands 71 between layers is easily formed. This is because when a new layer is formed on an existing layer, the molten metal constituting the new layer is easily cooled by the existing layer. Since the melting point of chromium contained in the molten metal is higher than that of copper, when the molten metal is cooled, chromium solidifies before copper. For this reason, an enriched layer 75 is formed between the existing layer and the new layer.
[0190] In the case of applying metal parts 7 produced by metal stacking molding to Fig.17 In the case of the fixed contact 91B and the movable contact 92B, it is preferable to arrange the enrichment layer 75 along the direction of current flow. In this case, the influence of the enrichment layer 75 on the function of the vacuum circuit breaker 9 can be reduced.
[0191] Description of Reference Numerals
[0192] 1 Atomizer
[0193] 10. Housing
[0194] 11 Divider
[0195] 12 Press-in device, 12r rod
[0196] 13 High frequency induction heating device, 13c coil
[0197] 14 Nozzle
[0198] 15 Recovery tank
[0199] 2 Raw materials and parts
[0200] 20 Melt
[0201] 3 Powder
[0202] 4 Particles
[0203] 40 Matrix
[0204] 41 Precipitate
[0205] 5. Resin
[0206] 6. Samples
[0207] 7 Metal parts
[0208] 70 base part, 71 island part
[0209] 75 enrichment layer
[0210] 9 Vacuum circuit breaker
[0211] 90 Vacuum valve
[0212] 91 Fixed terminal, 91A electrode rod, 91B fixed contact
[0213] 92 movable terminal, 92A electrode rod, 92B movable contact
[0214] 93 bellows, 94 arc shielding member.
Claims
1. A powder is an aggregate of multiple particles containing a metal element. Each of the plurality of particles comprises a matrix and a plurality of precipitates dispersed in the matrix. The matrix comprises a first component, The plurality of precipitates each contain a second component, The standard deviation of the content of the first component in the plurality of particles is 1.2 or less based on mass. The standard deviation of the content of the second component in the plurality of particles is 1.2 or less on a mass basis.
2. The powder according to claim 1, wherein The standard deviation of the average particle size of the plurality of precipitates in the plurality of particles is 0.1 or less.
3. The powder according to claim 1 or 2, wherein The first component and the second component are a combination having a two-liquid phase separation region in a phase diagram, The content ratio of the first component to the second component is a content ratio corresponding to the two-liquid phase separation region.
4. The powder according to any one of claims 1 to 3, wherein The average particle size of the plurality of particles is 200 μm or less.
5. The powder according to any one of claims 1 to 4, wherein The average particle size of the plurality of precipitates is 5 μm or less.
6. The powder according to any one of claims 1 to 5, wherein The maximum particle size of the plurality of precipitates is 20 μm or less.
7. The powder according to any one of claims 1 to 6, wherein The first component is copper, and the second component is chromium.
8. A metal component comprising a metal element, The metal component includes a base portion and a plurality of island portions dispersed in the base portion. The base portion includes a first component, The plurality of islands respectively contain a second component, The average particle size of the plurality of island portions is 10 μm or less.
9. The metal component according to claim 8, wherein: The standard error of the average particle size of the plurality of island portions in a plurality of different observation fields is 0.3 or less.
10. The metal component according to claim 8 or 9, wherein: The first component and the second component are a combination having a two-liquid phase separation region in a phase diagram.
11. The metal component according to any one of claims 8 to 10, wherein The first component is copper, and the second component is chromium.
12. The metal component according to any one of claims 8 to 11, wherein The content ratio of the first component to the second component is a content ratio corresponding to a two-liquid phase separation region in a phase diagram.
13. An electric contact, comprising the metal component according to any one of claims 8 to 12.
14. A method for producing a powder, comprising: Step A, preparing a raw material component including a first component and a second component; Step B, melting the raw material component by a high-frequency induction heating device without a crucible; and In step C, the molten liquid obtained in step B is powdered by atomization.
15. The method for producing a powder according to claim 14, wherein: The material component is a powder compact including a first solid in a powder state having the first component as a main component and a second solid in a powder state having the second component as a main component.
16. The method for producing a powder according to claim 14 or 15, wherein: The first component and the second component are a combination having a two-liquid phase separation region in a phase diagram, The content ratio of the first component to the second component in the raw material part is a content ratio corresponding to the two-liquid phase separation region, The temperature of the molten liquid is equal to or higher than the temperature of the two-liquid phase separation region in the phase diagram.
17. The method for producing a powder according to any one of claims 14 to 16, wherein: The first component is copper, and the second component is chromium. 18 . A method for producing a metal component, comprising: producing a powder compact by pressure-compacting the powder according to claim 1 , and producing the metal component by sintering the powder compact.
19. A method for producing a metal component, comprising producing the metal component by metal layered molding using the powder according to any one of claims 1 to 7.
Citation Information
Patent Citations
Cu-Cr alloy containing trace amount of Bi element and solidification preparation method thereof
CN108456798A
Laser selective melting forming method of copper-chromium alloy part
CN109759584A
A method for the production of materials for contact members
GB2066298A
Material for electrical contact and manufacture thereof
JP1992095318A
Manufacture of electrode material
JP1993217473A
